Efficacy of Flapless Corticotomy Accomplished by Piezosurgey in Accelerating Orthodontic Decrowding in Adults (Randomized Controlled Trial) (Journal of Hama University, 2021)
The duration of orthodontic treatment is considered one of the most challenges facing orthodontists, which may be a reason for refusing to undergo the treatment. Although these surgical procedures have proven their effectiveness, they are considered aggressive and may be faced by patient rejection because of the anxiety and fear of pain and due to surgery. Several techniques have been developed, such as Piezocision in attempt to weaken the cortical bone to accelerate orthodontic tooth movement. Evaluate the effectiveness of piezocision in acceleration decrowding of severe anterior mandibular teeth.The Sample consisted of 26 patients (12 male, 14 female) with an age range from 18 to 26 years. They were randomly divided into two equal groups, Group A is piezocision, Group B is conventional orthodontic treatments. Little irregularity index  changes were studied using dental cast in four time points before inserting the first archwire (T0), after 1 month of treatment onset  (T1), after 2 months (T2), and at the end of the alignment stage (T3).The overall treatment time needed to complete anterior alignment of the dental mandible arch was reduced compared with conventional orthodontic treatment(P